Supramolecular Differentiation for Construction of Anisotropic Fullerene Nanostructures by Time-Programmed Control of Interfacial Growth - Bairi, Partha; Minami, Kosuke; Hill, Jonathan P; Nakanishi, Waka; Shrestha, Lok Kumar; Liu, Chao; Harano, Koji; Nakamura, Eiichi; Ariga, Katsuhiko (ACS nano, 2016)
Supramolecular assembly can be used to construct a wide variety of ordered structures by exploiting the cumulative effects of multiple noncovalent interactions. However, the construction of anisotropic nanostructures remains subject to some limitations. Here, we demonstrate the preparation of anisotropic fullerene-based nanostructures by supramolecular differentiation, which is the programmed control of multiple assembly strategies. We have carefully combined interfacial assembly and local phase separation phenomena. Two fullerene derivatives, PhH and C12H, were together formed into self-assembled anisotropic nanostructures by using this approach. This technique is applicable for the construction of anisotropic nanostructures without requiring complex molecular design or complicated methodology.